SDGs and Islamic Cultural Heritage in Indonesia: Cultural, Local Wisdom, Islamic Law, and Customary Perspectives - Lukman Yafi; Nawwal Tattaqillah; Nahya Kazamzam Warumman (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to examine Islamic cultural heritage in Indonesia from cultural, local wisdom, Islamic law, and customary perspectives while connecting these dimensions with the SDGs. Theoretical framework: The study adopts an integrative theoretical framework combining cultural acculturation theory, Islamic legal perspectives, and museological approaches to heritage preservation. This framework explains how Islamic values interact with Malay local traditions and customary norms (adat), forming a distinctive socio-cultural system that reflects the harmony between religion, and culture. Literature review: The literature also discusses the role of museums as cultural institutions responsible for safeguarding tangible and intangible heritage. Furthermore, recent scholarship emphasizes the importance of digitalization and globalization in strengthening cultural preservation and ensuring the sustainability of heritage practices in line with the SDGs. Methods: This research employs a qualitative descriptive-analytical method. Data were collected through literature reviews, field observations, and semi-structured interviews with historians, museum curators, traditional leaders, and cultural practitioners in Sumatera Indonesia. The collected data were analyzed thematically to identify patterns of Islamic cultural heritage preservation and its relationship with local wisdom and Islamic legal values. Results: The findings indicate that Islamic heritage in Sumatera Indonesia can be classified into five categories: ancient manuscripts (25%), art and architecture (10%), religious traditions (25%), historical institutions and mosques (20%), and material artifacts (20%). The Gentala Arasy Museum plays a crucial role in heritage preservation with an educational effectiveness level of 80.11%. Cultural acculturation between Islam and Malay traditions has produced unique cultural expressions such as Assyuro rituals, zapin dance, batik with Islamic motifs, and traditional seloko reflecting Sharia-based ethical values. Implications: The study underscores the importance of strengthening heritage preservation through digitalization and multi-stakeholder collaboration involving government institutions, cultural communities, and academic organizations. These strategies contribute to SDGs related to cultural sustainability, and inclusive societies. Novelty: The novelty of this research lies in its integrative analysis linking Islamic cultural heritage with SDGs through cultural, legal, and customary perspectives while highlighting the innovative role of the Gentala Arasy Museum in promoting sustainable preservation of Islamic-Malay heritage in Indonesia.